Primary HIV Infection in Patients with Acute Hepatitis B: A Report of Two Cases. Issue 2 (February 2018) - Binda, Francesca; Monge, Elisa; Simonetti, Francesco R; Zanchetta, Nadia; Galli, Massimo; Milazzo, Laura; Corbellino, Mario; Antinori, Spinello
We describe two patients admitted to our institution with a diagnosis of sexually acquired acute hepatitis B who also had underlying hyper acute HIV infection. Both individuals reported high rates of condomless sex. Antiviral therapy active against HBV and HIV was started within days after diagnosis. Treatment was well tolerated and led to a rapid control of both infections and hepatitis B surface antibody seroconversion. The efficacy and safety of contemporary antiretroviral drug combinations suggest that treatment of acute HIV infection is feasible in patients with acute hepatitis B.